Learning Semantic in English Conversations - Muhammad Rizky Aziz; Rama Garetha Evansam (JOSAR (Journal of Students Academic Research), 2016)
This paper amis to analyze the learning semantic in English conversation, learning semantic which is a part of applied linguistic that focuses on the meaning, In addition there are manythigs toknow about semantic in English conversation what the important is, when the communication will not be able to deliver well which are about culture, accent, country. They are some aspects that we have to study about semantic in English conversation, in this paper, the writer use method of the research by using qualitative that is about the people habbit and when they have to communicate each othe. Because English is an international language, all of people should be able to communicate in English to express or mention something, to study abroad, to write an international paper, to join a conference, they need this language to do it.